A SUPPORTING HAND IN DEALING WITH INTERPERSONAL CONFLICTS: THE ROLE OF INTERACTIONAL JUSTICE - Nurul Ain Hidayah Abas; Kathleen Otto; Ramayah Thurasamy (Asian Academy of Management Journal, 2018)
Studying the styles in managing conflicts is critical in preventing the detrimental effects of interpersonal conflicts on employees’ well-being. In a sample of 390 Malaysian public sector subordinates, the relationships between conflict management styles (bargaining and problem solving) and psychological strain (somatic strain and depressive symptoms) was explored. Based on social exchange theory, it was further expected interactional justice to work as a moderator in this relationship, buffering the negative consequences of bargaining styles for subordinates with supervisors whom are having high rather than low interactional justice. Results indicate that bargaining was positively associated with somatic strain, while problem-solving was negatively associated with both somatic strain and depressive symptoms. As hypothesised, the PLS-SEM product moderator indicator approach analysis revealed that perceived interactional justice buffered the negative consequences of bargaining styles on somatic strain and depressive symptoms. This study’s primary novelty is to highlight interactional justice as a “helping hand” protecting against the negative consequences of bargaining styles among subordinates. Consequently, it has a main practical implication for organisational management aimed at sustaining the wellbeing for their manpower.